SLC11A1 polymorphisms and host susceptibility to cutaneous leishmaniasis in Pakistan. Issue 1 (December 2017) - Sophie, Mariam; Hameed, Abdul; Muneer, Akhtar; Samdani, Azam; Saleem, Saima; Azhar, Abid
Abstract Background The vector-borne cutaneous leishmaniasis (CL) is endemic in several regions of Pakistan mainly affecting poor populations. Host genetic factors, particularlySLC11A1 (solute carrier transmembrane protein) within macrophages, play a crucial role in disease pathology and susceptibility. Association ofSLC11A1 with cutaneous leishmaniasis, a neglected tropical disease, is not well established. Inconsistencies have been observed within different populations worldwide with respect to genetic susceptibility. This study was designed to investigate genetic variation(s) inSLC11A1 and to assess possible association with cutaneous leishmaniasis in Pakistan. Results Eight polymorphisms (rs2276631, rs3731864, rs2290708, rs2695342, rs201565523, rs17215556, rs17235409, rs17235416) were genotyped acrossSLC11A1 in 274 patients and 119 healthy controls. Six polymorphisms were studied by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and sequencing. Two single nucleotide polymorphisms were analyzed with newly designed semi-nested PCR assays. Case-control analysis showed no association between selected polymorphisms inSLC11A1 and cutaneous leishmaniasis. No significant difference was observed in the distribution of alleles between leishmaniasis patients and healthy individuals. Strong pairwise linkage disequilibrium was observed between rs2276631 and rs2290708 (r 2 = 64); and rs17235409 and rs17235416 (r 2 = 78). Conclusions This study shows that genetic variations in the candidate geneSLC11A1 do not affect susceptibility to cutaneous leishmaniasis in the sample population from Pakistan.